A Careful Balance: Materialist Concern Meets Spiritual Function in Balkh, Afghanistan - Wyndham, Constance (Material religion, 2019)
This article outlines the Aga Khan Trust for Culture's heritage preservation practices at the shrine of Khwaja Parsa in Balkh, Afghanistan. It explores how this organization's approach to the preservation of authenticity supports both classic preservation principles whilst also showing allegiance to Islamic practices that are compatible with the way this mosque and shrine complex is used in Balkh. One focus of the critical approach to heritage research has been on describing the tension between a preservationist' approach to heritage work - with its attached focus on the values of materiality, monumentality and aesthetics - and an approach that shows allegiance to religious or spiritual traditions that make sense in situ. This paper argues against this constructed dichotomy to reveal how the Aga Khan Trust for Culture's heritage work in Balkh empowers a hybridized, vernacularized heritage preservation practice that reflects both this organisation's worldview and political objectives.